Incretin Therapy – Present and Future (The Review of Diabetic Studies, 2023)
Although newer treatments for type 2 diabetes (T2D) patients have produced continual improvements in outcome, a large and growing population with prediabetes remains under-treated. In the last few years, incretin-based therapies have become an important treatment option for patients with T2D. There are two classes of incretin agents: the dipeptidyl peptidase-4 (DPP-4) inhibitors and the glucagon-like peptide 1 (GLP-1) receptor agonists. The ultimate goal of agents within both of these classes is to increase GLP-1 signaling, which results in augmented glucose-induced insulin secretion, inhibition of glucagon secretion, and decreased appetite. This should result in improved regulation of glucose homeostasis. GLP-1 receptor agonists enable patients to achieve significant weight loss. In contrast, DPP-4 inhibitors result in a less dramatic increase in GLP-1 levels; therefore, they are weight neutral. Incretin therapies are currently recommended for use early in the treatment algorithm for T2D patients whose disease is not manageable by diet and exercise alone, but the potential for these agents may be farther reaching. Current studies are evaluating the potential benefits of combining incretin therapies with basal insulin to provide continuous glucose control before and after meals. In addition, these agents may be promising for patients with prediabetes since they effectively reduce glycosylated hemoglobin levels and fasting plasma glucose levels, enable weight control, and have the potential to preserve β-cell function. Clearly, all of these properties are desirable for patients with prediabetes.